Hypoxic microenvironment shapes HIV-1 replication and latency - Zhuang, X; Pedroza-Pacheco, I; Nawroth, I; Kliszczak, AE; Magri, A; Paes, W; Rubio, CO; Yang, H; Ashcroft, M; Mole, D; Balfe, P; Borrow, P; et al. (Nature Research, 2020)
Viral replication is defined by the cellular microenvironment and one key factor is local oxygen tension, where hypoxia inducible factors (HIFs) regulate the cellular response to oxygen. Human immunodeficiency virus (HIV) infected cells within secondary lymphoid tissues exist in a low-oxygen or hypoxic environment in vivo. However, the majority of studies on HIV replication and latency are performed under laboratory conditions where HIFs are inactive. We show a role for HIF-2α in restricting HIV transcription via direct binding to the viral promoter. Hypoxia reduced tumor necrosis factor or histone deacetylase inhibitor, Romidepsin, mediated reactivation of HIV and inhibiting HIF signaling-pathways reversed this phenotype. Our data support a model where the low-oxygen environment of the lymph node may suppress HIV replication and promote latency. We identify a mechanism that may contribute to the limited efficacy of latency reversing agents in reactivating HIV and suggest new strategies to control latent HIV-1.